Survey dataset on presenteeism, job demand and perceived job insecurity: The perspective of diplomatic officers - Mokhtar, Daniella (Data Brief, 2020)
This data belongs to a sample of 347 diplomatic officers from two different locations which are the National Institute of Public Administration (INTAN) in Johor and Terengganu. This data consists of the demographic characteristics of the sample and three main variables. Each variable has sub-dimension which are (1) presenteeism: ability to complete a task and avoid disturbance, (2) job demand: workload, emotional and cognitive demand, (3) job insecurity: the importance and probability of an event to take place. The data were collected using a cross-sectional questionnaire via paper-and-pencil mode and was analyzed using SPSS version 22. Pearson correlation analyses revealed a significant relationship between avoiding disturbance (sub-dimension of presenteeism) and the probability of an event happening (sub-dimension of job insecurity) and no significant correlation between other variables. Analyses of the data can provide insights into determinants of presenteeism that may be useful for researchers in the field and policymakers that are interested in this area. It may serve as a reference to expand research and to develop interventions to facilitate productivity and well-being in the workplace.